A Battery‐ and Leadless Heart‐Worn Pacemaker Strategy. (11th May 2020) - Yi, Zhiran; Xie, Feng; Tian, Yingwei; Li, Ning; Dong, Xiaoxue; Ma, Ye; Huang, Yue; Hu, Yili; Xu, Xiaobin; Qu, Dan; Lang, Xilong; Xu, Zhiyun; et al.
Abstract: Over the past half‐century, cardiac pacing technology has adhered to one basic system. However, many pacemaker‐related complications are related to this system, particularly in terms of the power supply and leads. Here, for the first time a heart‐worn pacemaker strategy is presented, which allows batteryless powering and leadless pacing. The batteryless feature is attained via heart‐extrusion energy scavenging through a micromachined piezoelectric thick film transducer. A record in vivo output current of 30 µA is obtained in an adult swine by the implanted piezoelectric transducer, which can effectively drive a commercial cardiac pacemaker. The exocardial pacing method is demonstrated by this batteryless pacemaker functions without a device or leads placed within the cardiac chambers. Lead‐ or batteryless options are being explored as new basic features of cardiac pacemakers. The presented heart‐worn pacemaker strategy may be useful in future pacing technology. Abstract : A heart‐worn pacemaker strategy with battery‐ and leadless features is proposed based on piezoelectric heart‐extrusion energy scavenging and exocardial pacing approaches. Batteryless or leadless is being explored as the new basic feature of the cardiac pacemaker. This strategy may provide new insights for the development of future pacemakers.